Gender Representation in Elementary School Kemuhammadiyahan Education Books (Critical Discourse Analysis Cover of Class III-VI Kemuhammadiyahan Education Books) - Kurniawan, Rio (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Constitutional guarantees and various formal policies cannot in themselves create gender equality and justice in real life. In reality, there are still various forms of gender inequality in various aspects of life. This is also found on the cover of the Kemuhammadiyah education book at the elementary school level. This research is a library research. The analysis used is critical discourse analysis. The aims of this research are as follows: to find out the critical discourse analysis of the Kemuhammadiyahn Education book cover grades III to VI; know the representation of gender and the role of women in the cover of Kemuhammadiyahan education books for grades III to VI. The results of the study explained that the male dominance was 79% and 21% female. Representation of social roles for men is displayed 82% in the public domain and for women 18% in the public domain.